Renewal In Guidance Of Quran Readings - ALmashhdany, Mohammed E. (Humanities Journal of University of Zakho, 2013)
The present study deals with renewal aspects in guidance of Quran. It consists of an introduction, preface, five chapters, conclusion and references. The introduction shows the importance of such subject, framework of study and the sample under analysis. The concept of guidance and its development are given in the preface. The first chapter deals with the stage of potential guidance. The second chapter deals with the stage of intended guidance. The third chapter tackles the stage of gathering guidance. The fourth chapter deals with the stage of specialist guidance. Finally, the fifth chapter deals with the stage of reactions guidance. After that, we talks about the most important results and giving a list of maim references.